ANALISIS PERWATAKAN DALAM NOVEL SURAT KECIL UNTUK TUHAN KARYA AGNES DAVONAR - Desputri, Sherly; Bahardur, Iswadi; Hartati, Yulia Sri (Pendidikan Bahasa Indonesia, 2013)
This study focused on the characterization in the novel Small Letters to God Agnes Davonar work. Formulation of the research problem